ANALISIS PUTUSAN PENGADILAN AGAMA BANTAENG TENTANG PEMBERIAN DISPENSASI PERKAWINAN ANAK DIBAWAH UMUR (STUDI PUTUSAN: PUTUSAN PENGADILAN AGAMA BANTAENG NOMOR 42/PDT.P/2018/PA.BATG ATAS PEMBERIAN DISPENSASI PERKAWINAN ANAK DIBAWAH UMUR) - Chika Angelica Awaloei; Mia Hadiati (Fakultas Hukum Universitas Tarumanagara, 2019)
Children are the next generation of our great country. Therefore, it is the country’s responsibility to protect children’s rights by creating regulations to enforce it. One amongst many of the regulations is UU No.1 Tahun 1974 tentang Perkawinan where it is stated in Pasal 7 ayat 1 that the minimum age of marriage is nineteen years old for male and sixteen years old for female. However, in 2019 with many considerations, Mahkamah Konstitusi ratified UU No. 16 Tahun 2019. Which means, the minimum age of marriage rose to nineteen years old for both male and female. Nevertheless, a judge in Bantaeng, South Sulawesi, decided to grant a request for dispensation of a matrimony between a fifteen years old male and fourteen years old female. The judge’s consideration was so the female child can have a protection. The writer perceives this decision as injudicious because it is fair to say that physically, mentally, and financially, this couple is not ready for marriage. Also, by uniting them in marriage, both the female and male child will be at risk of losing certain rights that they suppose to receive as children.